2007
DOI: 10.1007/s00330-007-0789-5
|View full text |Cite
|
Sign up to set email alerts
|

Drug-eluting stents in renal artery stenosis

Abstract: Because of higher acute and long-term success rates compared with balloon angioplasty alone, percutaneous stent implantation has become an accepted therapy for the treatment of atherosclerotic renal artery stenosis. Restenosis rates after successful renal stent placement vary from 6 up to 40%, depending on the definition of restenosis, the diameter of the treated vessel segment and comorbidities. The safety and efficacy of drug-eluting stents for the treatment of renal-artery stenosis is poorly defined. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…Further, the drug-eluting stent is more costly than the bare-metal stent and likely will need long-term antiplatelet therapy with aspirin and clopidogrel. 31 Concerns have also been raised about the durability of the thinner coronary stents in the renal arteries that may lack the radial strength needed to overcome the increased potential for elastic recoil of aorto-ostial renal artery stenosis. 22 The current use of coronary drug-eluting stents in renal arteries is also limited by the 4-mm maximum size of available stents, although the directions for use for some of these stents (ION and Promus) state that they can be dilated to 5.75 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the drug-eluting stent is more costly than the bare-metal stent and likely will need long-term antiplatelet therapy with aspirin and clopidogrel. 31 Concerns have also been raised about the durability of the thinner coronary stents in the renal arteries that may lack the radial strength needed to overcome the increased potential for elastic recoil of aorto-ostial renal artery stenosis. 22 The current use of coronary drug-eluting stents in renal arteries is also limited by the 4-mm maximum size of available stents, although the directions for use for some of these stents (ION and Promus) state that they can be dilated to 5.75 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Bifurcation lesions are frequent in coronary arteries, and treatment with a stent is common even though it is difficult (7). Studies from the bare-metal stent (BMS) era consistently demonstrated that the one-stent approach was superior to the two-stent approach; this view remains controversial in the DES era (8). Although two-stent strategy has not been proven to be superior in the treatment of coronary arteries, this might not be true in renal artery stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Eine Bedeutung im klinischen Alltag haben DES in der NAST-Therapie bisher nicht erreicht [29]. Umfangreichere Erfahrung gibt es für DES bei der InStent-Restenose [24].…”
Section: Zukünftige Studienunclassified